ANTIVIRAL ACTIVITY OF CASHEW NUT SHELL EXTRACT AGAINST COWPEA MILD MOTTLE VIRUS ON SOYBEAN - Andayanie, Wuye Ria; Nuriana, Wahidin; Ermawati, Netty (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Antiviral Activity of Cashew Nut Shell Extract Against Cowpea mild mottle virus on Soybean. Cowpea mild mottle virus (CPMMV) is one of important virus on soybean. Management of CPMMV is usually by controlling its vector using insecticide which has adverse effect on environmental and non target insect. Therefore, it is important to find an alternative control which is environment friendly such as utilizing of plant extract. Cashew nut shell (CNS) is a waste during processing of cashew nut and reported containing some antimicrobe substances. The research was aimed to evaluated the potency of CNS extract as antiviral against CPMMV. The experiment was designed by Randomized Block Design with 4 replicates and each treatment unit consisted of 10 plants. The application method (prior and post virus inoculation, mixing of virus sap and CNS extract) and concentration of CNS extract (0.75 %; 1.5 %; 3.0 %; 6.0 %) were evaluated the effectiveness of their combination to inhibit CPMMV infection. The application of CNS extract were abled to decreased disease incidence and increase incubation period compared to untreated with CNS extract. and severity of treated plants significantly. However, plants treated with concentration 3.0 % and 6.0 % prior virus inoculation and mixing CNS extract with concentration 1.5 %, 3.0 %, and 6.0 % with CPMMV sap showed that the virus titre was negatively detected by ELISA using CPMMV antisera. It is indicated that the potential of CNS extract as antiviral. All treatments combination able to suppress virus infection without phytotoxicity effect, except CNS 6.0 % treatment.